Predicting group of metabolites available in partially purified tomato leaves extract showing anticancer activity by HPLC and FTIR - Wan Chik, Wan Dalila; Amid, Azura; Jamal, Parveen (2011)
Previously, tomato leaves have been proved to be one of the potential anticancer agents. High Performance Liquid Chromatography (HPLC) and Fourier transform infrared (FTIR) spectroscopic instrumentation was used to predict the presents of group of metabolites and to assign the possibility of certain absorption bands, in which most of the peaks in partially purified tomato (Solanum lycopersicon) leaves methanol extract are attributable to the specific functional groups. The extraction was carried out in a shake flask by 82% methanol, 1:10(w/v)sample to solvent ratio, agitated at 22°C with 110 rpm within 24 hours. Later, the extract was partially purified by column chromatography. High Performance Liquid Chromatography (HPLC) is used to quantify the number of unknown component presents in the fraction. Then, a FT-IR Bruker Tensor 27 System was used during FTIR data acquisition. The collection of FTIR spectra was carried out at 16 scans with resolution of 4 cm-1using strong apodization in the frequency regions of 4,000–650 cm-1. The results support the premise that HPLC and FTIR spectroscopy are efficient and accurate methods for determining major and minor components presents in the extract.